Nano-microsphere loaded with astaxanthin and preparation method thereof

Through the combination of zein, lecithin and chitinoligosaccharides, nano microspheres loaded with astaxanthin were formed, which solved the problem of low gastrointestinal stability and bioavailability in the gastrointestinal tract and achieved its in-water phase Efficient delivery and stability improvement in the environment.

CN119280182APending Publication Date: 2025-01-10JIMEI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411300974.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Astaxanthin has poor stability in the gastrointestinal tract and is difficult to dissolve in the aqueous environment, resulting in low bioavailability and the existing nano-embedded delivery system is not perfect.

Method used

Zein and lecithin are self-assembled through anti-solvent method to form a complex, and chitosaccharides are added to form nano-microspheres loaded with astaxanthin through electrostatic action, improving their water solubility and stability.

Benefits of technology

It significantly improves the water solubility, stability and biological allowability of astaxanthin, extends the half-life of photodegradation, enhances antioxidant activity and assists in lowering blood lipids.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005047656510000051
    Figure BDA0005047656510000051
  • Figure BDA0005047656510000052
    Figure BDA0005047656510000052
  • Figure BDA0005047656510000053
    Figure BDA0005047656510000053
Patent Text Reader

Abstract

The invention provides a nanometer microsphere loaded with astaxanthin and a preparation method of the nanometer microsphere. The method comprises the following steps: dissolving zein in an ethanol solution, then adding lecithin and stirring to obtain a zein-lecithin compound; astaxanthin is added into the zein-lecithin compound to be stirred, and then zein-lecithin-astaxanthin nano microspheres are prepared through an anti-solvent method by taking water as an anti-solvent; adding the zein-lecithin-astaxanthin nano-microspheres into a chitosan oligosaccharide solution, stirring, and adjusting the pH value to 4.0, so as to obtain the astaxanthin-loaded nano-microspheres. The nano-microspheres can effectively encapsulate astaxanthin, and the water solubility, stability, biological availability and biological activity of astaxanthin are improved; a reference can be provided for preparing an astaxanthin-loaded delivery carrier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of active ingredient delivery systems, and in particular to nano-microspheres loaded with astaxanthin and a preparation method thereof. Background Art

[0002] Astaxanthin (AST) is a fat-soluble carotenoid with biological activities such as anti-inflammatory, anti-tumor, anti-obesity, cardioprotection, and prevention and repair of light damage, and has high commercial value. However, AST is poorly soluble in water, easily degraded under conditions such as light and high temperature, and has poor stability in the gastrointestinal tract. In addition, AST is a fat-soluble molecule and is difficult to dissolve in the aqueous environment of the gastrointestinal tract, which greatly reduces the bioavailability of AST. Therefore, improving the water solubility and stability of AST and improving its bioavailability are hot issues in the field of AST research.

[0003] At present, protein-based delivery systems have attracted attention due to their advantages such as non-toxicity and biodegradability. They can effectively encapsulate bioactive substances and improve their water solubility, stability and bioavailability. However, studies have shown that the delivery system composed of pure protein will reduce the bioavailability of the encapsulated fat-soluble bioactive substances because it does not contain lipids. Liposomes are mainly used as delivery carriers for fat-soluble bioactive substances, which can improve the bioavailability of the encapsulated fat-soluble bioactive substances. However, liposomes have poor stability and are prone to rupture and aggregation, resulting in the loss of bioactive substances. Therefore, the existing AST nano-encapsulation delivery system is not perfect. Summary of the invention

[0004] The present invention aims to solve the key technical problems in the research and development of the above products to a certain extent.

[0005] To this end, in a first aspect of the present invention, the present invention provides a method for preparing nanoparticles loaded with astaxanthin, which comprises the following steps:

[0006] S1, dissolving zein in an ethanol solution, then adding lecithin and stirring to obtain a zein-lecithin complex;

[0007] S2, adding astaxanthin to the zein-phosphatidylcholine complex and stirring, and then using water as an anti-solvent to prepare zein-phosphatidylcholine-astaxanthin nanoparticles by an anti-solvent method;

[0008] S3, adding zein-phosphatidylcholine-astaxanthin nanoparticles into the chitosan oligosaccharide solution, stirring, and adjusting the pH to 4.0 to obtain nanoparticles loaded with astaxanthin.

[0009] According to the preparation method of the present invention, the method uses zein and lecithin to self-assemble through an antisolvent method to form a zein-lecithin complex, and then adds chitosan oligosaccharide to bind to the zein-lecithin complex in an electrostatic way to form zein-lecithin-chitosan oligosaccharide nanospheres, and uses this as a delivery carrier for astaxanthin to form zein-lecithin-chitosan oligosaccharide loaded astaxanthin nanospheres. The method can effectively encapsulate astaxanthin and improve the water solubility, stability, bioavailability and biological activity of astaxanthin.

[0010] In the second aspect of the present invention, the above-mentioned preparation method is provided to prepare nanoparticles loaded with astaxanthin.

[0011] The nano-microspheres are in a spherical core-shell structure, and astaxanthin exists in an amorphous state in the nano-microspheres.

[0012] The nanospheres were treated with ultraviolet light and stored in the dark at 4°C and 25°C for 28 days. The results showed that the photodegradation and storage degradation of astaxanthin in the nanospheres followed first-order kinetics. Compared with free astaxanthin, the photodegradation kinetic constant under ultraviolet light treatment decreased by 92.3%, and the half-life under storage conditions of 4°C and 25°C increased by 6.1 and 5.1 times, respectively.

[0013] The effect of the nanoparticles on the digestion and absorption of astaxanthin was investigated through simulated gastrointestinal digestion and Caco-2 cell absorption experiments. The results showed that the retention rate of the nanoparticles was 86.7% and the bioavailability was 69.5%; the absorption of the nanoparticles before simulated gastrointestinal digestion was 1.8680 ng / mg protein and after digestion was 3.1900 ng / mg protein.

[0014] By ABTS ·+ The antioxidant effect of the nanoparticles and their digestion products was investigated using the DPPH method and Caco-2 cell oxidative stress model. The results showed that the nanoparticles had the highest antioxidant activity. The high-fat model established using HepG2 cells was used to explore the auxiliary lipid-lowering activity of the nanoparticles and their digestion products. The results showed that the nanoparticles had the best auxiliary lipid-lowering activity.

[0015] In the third aspect of the present invention, there is provided the use of the above-mentioned astaxanthin-loaded nanoparticles in delivering astaxanthin.

[0016] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is the AST standard curve according to an embodiment of the present invention;

[0018] Figure 2 The effects of different zein to lecithin mass ratios on microsphere particle size (A), PDI (A) and Zeta potential (B) according to the embodiments of the present invention;

[0019] Figure 3 The effect of different zein and lecithin mass ratios on microsphere embedding efficiency according to the embodiments of the present invention;

[0020] Figure 4 The effect of different zein to lecithin mass ratios on the photostability of microspheres according to the embodiments of the present invention;

[0021] Figure 5 The effect of different zein to lecithin mass ratios on the temperature stability of microspheres according to the embodiments of the present invention;

[0022] Figure 6 The effects of different lecithin to chitosan oligosaccharide mass ratios on microsphere particle size (A), PDI (A) and Zeta-potential (B) according to the embodiments of the present invention;

[0023] Figure 7 The effect of different lecithin and chitosan oligosaccharide mass ratios on microsphere embedding efficiency according to the embodiments of the present invention;

[0024] Figure 8 The effects of different lecithin and chitosan oligosaccharide mass ratios on the photostability of microspheres according to the embodiments of the present invention;

[0025] Fig. 9 The effect of different lecithin and chitosan oligosaccharide mass ratios on the temperature stability of microspheres according to the embodiments of the present invention;

[0026] Fig.10 A full wavelength scanning comparison diagram of the solution before and after AST embedding according to an embodiment of the present invention;

[0027] Fig.11 is an XRD spectrum according to an embodiment of the present invention;

[0028] Fig.12 DSC spectra of AST (A), Z / AST, Z / L / AST, and Z / / L / C / AST (B) according to the embodiments of the present invention;

[0029] Fig.13 TEM image of Z / L / C / AST nanospheres according to an embodiment of the present invention;

[0030] Fig.14 The effect of AST on the ultraviolet spectrum of zein according to an embodiment of the present invention;

[0031] Fig.15 The fluorescence spectra of the interaction between AST and Zein (A) and Zein-Lecithin (B) according to an embodiment of the present invention;

[0032] Fig.16 The Stern-Volmer curve diagram of the interaction between AST and Zein (A) and Zein-Lecithin (B) according to an embodiment of the present invention;

[0033] Fig.17 A double logarithmic curve diagram of the interaction between AST and Zein (A) and Zein-Lecithin (B) according to an embodiment of the present invention;

[0034] Fig.18 The Van't Hoff diagram of the interaction between AST and Zein (A) and Zein-Lecithin (B) according to an embodiment of the present invention;

[0035] Fig.19 A molecular docking diagram of AST and Zein-Lecithin according to an embodiment of the present invention;

[0036] Fig. 20 The effect of urea, sodium dodecyl sulfate and sodium chloride on the turbidity of Zein-Lecithin (A) and Lecithin-COS (B) complexes according to an embodiment of the present invention;

[0037] Fig.21 is a Fourier transform infrared spectrum diagram according to an embodiment of the present invention;

[0038] Fig. 22 A schematic diagram of the preparation of Z / L / C / AST nanospheres according to an embodiment of the present invention and a description of the structure;

[0039] Fig.23 A logarithmic graph showing changes in AST concentration over time in different nanosystems according to an embodiment of the present invention;

[0040] Fig.24 The first-order kinetic diagrams of AST stored at 4°C (A) and 25°C (B) in different nanosystems according to the embodiments of the present invention;

[0041] Fig.25 is the retention rate of AST according to an embodiment of the present invention;

[0042] Fig.26 is the bioavailability of AST according to an embodiment of the present invention;

[0043] Fig. 27is the uptake of AST in the nanospheres by Caco-2 cells before and after simulated gastrointestinal digestion according to an embodiment of the present invention;

[0044] Fig.28 ABTS of Z / AST, Z / L / C, Z / L / C / AST and free AST at different AST concentrations according to an embodiment of the present invention ·+ Clearing ability;

[0045] Fig.29 DPPH of Z / AST, Z / L / C, Z / L / C / AST and free AST according to different AST concentrations according to the embodiment of the present invention · Clearing ability;

[0046] Fig.30 The antioxidant activity of the simulated digestion products of free AST, Z / AST and Z / L / C / AST in vitro according to the embodiments of the present invention;

[0047] Fig.31 Effects of Z / AST (A), Z / L / C / AST (B), H2O2 (C), Z / AST digestion solution (D) and Z / L / C / AST digestion solution (E) on Caco-2 cell viability according to the embodiments of the present invention;

[0048] Fig.32 The effects of free AST and nano-microspheres and digestive fluid thereof on ROS in Caco-2 cells according to the embodiments of the present invention;

[0049] Fig.33 The effects of free AST and nano-microspheres and digestive fluid thereof on SOD (A) and CAT (B) in Caco-2 cells according to the embodiments of the present invention;

[0050] Fig.34 The effects of free AST and nano-microspheres and digestive fluid thereof on MDA in Caco-2 cells according to the embodiments of the present invention;

[0051] Fig.35 The effects of Z / AST (A), Z / L / C / AST (B), OA (C), Z / AST digestion solution (D) and Z / L / C / AST digestion solution (E) on HepG2 cell viability according to the embodiments of the present invention;

[0052] Fig.36 The figure shows the effects of free AST, nanospheres and their digestion products on blood lipid levels of HepG2 cells according to an embodiment of the present invention. DETAILED DESCRIPTION

[0053] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0054] The disclosure below provides many different embodiments or examples to realize different implementations of the present invention. In order to simplify the disclosure of the present invention, specific embodiments or examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the examples of various specific processes and materials provided by the present invention, those of ordinary skill in the art can be aware of the applicability of other processes and / or the use of other materials. Unless otherwise stated, the implementation of the present invention will adopt the conventional techniques in the fields of chemistry, molecular biology, etc. within the capabilities of those skilled in the art.

[0055] It should be noted that in the following embodiments:

[0056] Human hepatocellular carcinoma (HepG2) cells and human colorectal adenocarcinoma (Caco-2) cells were purchased from the Cell Bank of Type Culture Collection Committee of the Chinese Academy of Sciences (Shanghai).

[0057] 1. AST full wavelength scan: Dissolve AST in dichloromethane / ethanol solution to prepare a solution of a certain concentration, and perform full wavelength scan between 400nm-700nm.

[0058] 2. Establishment of AST standard curve: Accurately weigh 1 mg of AST standard and dissolve it in a trace amount of dichloromethane, and dilute it to a 100mL volumetric flask with anhydrous ethanol. Pipette 0.25mL, 0.50mL, 1.00mL, 2.00mL, 4.00mL, 6.00mL, 8.00mL, and 10.00mL into a 10mL volumetric flask and dilute it with anhydrous ethanol to obtain solutions with AST concentrations of 0.25mg / L, 0.50mg / L, 1.00mg / L, 2.00mg / L, 4.00mg / L, 6.00mg / L, 8.00mg / L, and 10.00mg / L. Determine the absorbance of AST solutions of different concentrations at a wavelength of 478nm. The AST standard curve is as follows: Figure 1 shown.

[0059] 3. Determination of particle size, PDI and Zeta potential: The particle size, polydispersion index (PDI) and Zeta potential of nanoparticles were measured by NS-90Z nanoparticle size analyzer. The operation steps are as follows: 1.0 mL of sample solution was added to the particle size sample cell or potential sample cell, stabilized at 25°C for 120 seconds, fixed the scattering angle at 90°, and started the measurement. Each sample was tested 3 times, and the final result was averaged.

[0060] 4. Determination of embedding rate: Pipette 0.5 mL of sample solution into a centrifuge tube, add n-hexane to extract until the extraction is complete, transfer the extract into a 10 mL brown volumetric flask, and finally adjust the volume to 10 mL. Measure its absorbance at a wavelength of 478 nm using an enzyme marker.

[0061]

[0062] 5. Light stability: Take 3 mL of sample in a quartz cuvette, place it in a light shield, set the UV lamp wavelength to 254 nm, the distance to 10 cm, and take samples after 60 min and 120 min of UV irradiation. Determine the AST content in the sample according to the method in step 4 above, and calculate the AST retention rate according to the following formula.

[0063]

[0064] 6. Temperature stability: Use water bath conditions of 65℃, 30min and 95℃, 15min to simulate the effects of pasteurization temperature and high temperature heating process on AST and AST-loaded composite microspheres. After the heat treatment, take out the sample from the constant temperature water bath immediately and place it in water to lower the sample temperature to room temperature. Determine the AST content according to the method in step 4 above, and calculate the AST retention rate according to the following formula.

[0065]

[0066] 7. X-ray diffraction (XRD): X-ray diffraction patterns of different samples were obtained using an X-ray diffractometer. The X-ray source was a copper anode, the experimental voltage was 40 KV, the experimental current was 40 mA, the detection speed was 2° / min, the step size was 0.02°, and the detection range was 5-60°. The liquid samples were vacuum dried before the experiment.

[0067] 8. Differential Scanning Calorimetry (DSC): The thermal properties of different samples were studied using a differential scanning calorimeter. The samples were heated from 30°C to 250°C at a rate of 10°C / min, and nitrogen was continuously purged at a rate of 40 mL / min.

[0068] 9. Transmission electron microscopy (TEM): The morphology of the microspheres was analyzed using a transmission electron microscope. A drop of nano-microsphere dispersion was placed on a 200-mesh carbon-coated copper grid, stained with 2% phosphotungstic acid, and the sample was photographed at a voltage of 200 kV.

[0069] 10. UV-Vis spectroscopy: Add 200 μL of AST-Zein or AST-Zein-Lecithin mixed system solution into a 96-well plate, and use a multifunctional microplate reader to measure the absorbance of the mixed system solution at 25°C and in the range of 200-320 nm.

[0070] 11. Intrinsic fluorescence spectrum: AST-Zein and AST-Zein-Lecithin mixed systems were prepared; the concentration range of AST in the mixed system was 0-21μM, and the concentration of Zein and Lecithin was 3μM. The mixed system was incubated at 298K, 304K and 310K for 30min, and then the fluorescence spectrum was measured. The excitation wavelength was 280nm, the scanning emission wavelength was 300nm-500nm, and the excitation and emission slit widths were fixed at 5nm.

[0071] 12. Reactive additives: Reactive additives known to affect specific types of molecular interactions (i.e., urea, sodium dodecyl sulfate, and sodium chloride) were used to analyze the interaction between Lecithin and Zein and Lecithin and COS. After adding urea, sodium dodecyl sulfate, or sodium chloride to the solution containing Zein and Lecithin and the solution containing the mixture of Lecithin and COS, the absorbance was measured at a wavelength of 650 nm to indicate turbidity.

[0072] 13. Fourier transform infrared spectroscopy (FTIR): The sample was mixed and ground with KBr at a volume ratio of 1:100, then pressed into a transparent sheet in a mold and measured with a FTIR spectrometer. The scanning wavelength range was 4000-400cm -1 .

[0073] 14. Molecular docking: Since the crystal structure of Zein is not included in the protein crystal structure database, homology modeling was performed to generate the structure of Zein. The amino acid sequence of Zein was obtained from NCBI. In the search results of the LOMETS program (https: / / zhanglab.med.umich.edu / LOMETS / ) of the RCSB protein database, the model with the highest confidence score was selected for molecular docking. The main component of Lecithin is phosphatidylcholine (PC), so PC was selected to bind to Zein to simulate the binding of Lecithin to Zein. The 2D and 3D structures of PC and AST were obtained from the PubChem database, with CIDs 5287971 and 5281244.

[0074] Molecular docking, visualization, and rendering simulations were performed using AutoDock 4.0 and AutoDockTools 1.5.4. The ligand binding site of the protein was defined by a 60 × 60 × 60 grid space.

[0075] 15. Photodegradation kinetics: Take samples in quartz cuvettes, place them in light-proof covers, set the wavelength of UV lamp to 254nm, and the distance to 10cm. Take 100μL of samples in 1.5mL centrifuge tubes at different times (0, 5, 15, 30, 50, 75, 105, 140, 180, 240, 300min), and store them in a foam box in an ice bath away from light. After sampling, add 900μL of dimethyl sulfoxide to each sample, vortex for 15s, and centrifuge at 10000×g for 3min. Measure the absorbance value of the supernatant at a wavelength of 478nm. The absorbance value is the relative concentration of AST. Take photos of the samples at regular intervals. Data processing, draw a logarithmic graph of absorbance, and calculate its degradation rate.

[0076] 16. Storage degradation kinetics: The samples were stored in the dark at 4°C and 25°C for 28 days, and the samples were taken out every 7 days to determine their AST retention rate.

[0077] 17. Simulated gastric digestion system: Prepare 5 mL of simulated gastric digestion solution (containing 0.75 mM CaCl 2 , 6.9mmol / LKCl, 0.9mmol / L KH 2 PO 4 , 25mmol / L NaHCO 3 , 47.2mmol / L NaCl, 0.1mmol / L MgCl 2 ·(H 2 O) 6 、0.5mmol / L(NH 4) 2 CO 3 , 4 g pepsin, pH = 3). 5 mL of the microsphere solution was mixed with an equal amount of simulated gastric fluid, the pH was adjusted to 3.0 with 1 M HCl, and digested at 37°C and 180 rpm for 2 h.

[0078] 18. Simulated intestinal digestion system: Prepare 10 mL of simulated intestinal digestion solution (containing 0.3 mM CaCl 2 , 6.8mmol / LKCl, 0.8mmol / L KH 2 PO 4 、85mmol / L NaHCO 3 , 38.4mmol / L NaCl, 0.33mmol / L MgCl 2 ·(H 2 O) 6 , 0.5 g pancreatic enzyme, 1.26 g pancreatic lipase, 10 mM bile salt, pH = 7), mixed with 10 mL simulated intestinal fluid after gastric digestion, the pH of the digestive fluid was adjusted to 7.0, and digested at 37°C, 180 rpm for 2 h.

[0079] 19. Analysis of AST retention rate: The retention rates of AST in Z / AST, Z / L / AST and Z / L / C / AST nanoparticles after simulated gastric and intestinal digestion were determined. During the simulated gastrointestinal digestion, 1 mL of digestion dispersion was drawn at the end of simulated gastric digestion and simulated gastrointestinal digestion, and 1 mL of dichloromethane and 1 mL of anhydrous ethanol were added to extract AST in the micellar phase. The mixture was vortexed for 30 seconds to allow for full contact and mixing. The organic phase was separated by centrifugation at 3000 × g for 3 minutes. The dichloromethane layer was collected and transferred to a 5 mL brown volumetric flask. The extraction was repeated three times until the extraction was complete. The 5 mL brown volumetric flask was fixed to volume and its absorbance was measured at a wavelength of 478 nm. According to the AST standard curve ( Figure 1 ) to calculate the AST content in the micellar phase. The retention rate of AST was calculated according to the following formula:

[0080]

[0081] Among them: A 1 A is the content of AST in digestive juice; 0 is the AST content in the initial sample.

[0082] 20. Analysis of AST bioavailability: After the simulated gastrointestinal digestion is completed, the digestion dispersion is immediately placed on ice to stop digestion, and 5 mL of the dispersion is centrifuged at 12000×g at 4°C for 30 min. The centrifugal system is divided into three phases: the bottom is an opaque precipitation phase, the middle is a mixed micelle phase, and the top is a thin oily or creamy phase. 1 mL of the micelle phase is drawn and the AST content in the micelle phase is determined. The bioavailability is calculated according to the following formula:

[0083]

[0084] Among them: A 1 is the content of AST in the micelle phase; A 0 It is the content of AST in digestive juice.

[0085] 21. Scavenging effect of nanospheres on ABTS free radicals: 7mM ABTS solution was mixed with 2.4mM K 2 S 2 O 8 The solutions were mixed in equal proportions and kept at room temperature in the dark for 16 h to prepare ABTS. + Before use, ABTS + 0.2M NaH 2 PO 4 -Na 2 HPO 4 (pH = 7.0) solution was diluted until its absorbance at 734 nm was 0.70 ± 0.02, which is ABTS· + Working fluid.

[0086] Add 0.1 mL of nanosphere solution or simulated digestion dilution solution to a 1.5 mL centrifuge tube, and then add 1 mL of ABTS. + The working solution was mixed evenly, and after being placed in a water bath at 37°C for 1 hour, the absorbance value A was measured at a wavelength of 734 nm. 1 , the absorbance value measured by replacing the sample solution with distilled water is A 0 , calculate the ABTS free radical scavenging rate of the sample according to the following formula.

[0087]

[0088] Among them: A 1 is the absorbance of the sample; A 0 is the absorbance of the blank (distilled water is used instead of the sample).

[0089] 22. The scavenging effect of nano-microspheres on DPPH free radicals:

[0090] The DPPH free radical scavenging capacity was determined using the DPPH free radical scavenging rate detection kit. Set up a blank tube, a sample test tube, and a sample control tube. Add 0.05 mL of microsphere solution or simulated digestion diluent to the sample test tube and the sample control tube, add 0.225 mL of anhydrous ethanol and 0.225 mL of DPPH working solution to the sample test tube, and add 0.45 mL of anhydrous ethanol to the sample control tube. Replace the sample solution with distilled water and operate as in the sample test tube. After 30 minutes of reaction in the dark, measure the OD 517 The DPPH free radical scavenging rate of the sample was calculated according to the following formula.

[0091]

[0092] Among them: A 0 = absorbance value of blank tube; A 1 = absorbance value of the sample measuring tube; A 2 = absorbance value of sample control tube.

[0093] 23. CCK-8 method to detect cell viability

[0094] The effects of Z / AST and Z / L / C / AST nanoparticles and simulated digestive fluid on the proliferation activity of Caco-2 cells were determined using CCK-8 assay. 4 Caco-2 cells were inoculated at a concentration of cells / well and cultured until the cell density reached 90%. The culture medium on the cell layer was discarded, and different concentrations of composite nanosphere solutions and simulated digestive fluid dilution (digestive fluid is the micelle phase in the simulated gastrointestinal digestion dispersion) were added to the Caco-2 cell monolayer at a volume of 100 μL / well and incubated at 37°C with 5% CO 2 The cells were cultured for 24 h under induction. The concentrations of Z / AST and Z / L / C / AST nanosphere solutions were 100, 200, 300, 400 and 500 μL / mL, and the concentrations of simulated digestive fluid were 10, 20, 30, 40 and 50 μL / mL.

[0095] After the culture was completed, 10% CCK-8 reagent was added to each well and incubated at 37°C in the dark for 1 hour. The absorbance was then measured at 450 nm using an ELISA reader. Cell viability was calculated according to the formula.

[0096]

[0097] In this formula, A 1 OD for the treatment group 450 The absorbance value of 2 OD for the control group 450 The absorbance value of 3 Represents the blank group OD450 The absorbance value.

[0098] 24. Establishment of Caco-2 cell oxidative damage model

[0099] The cells in the control group were added with 100 μL of ordinary DMEM growth medium; 2 O 2 Each well of the cells in the oxidative damage group was added with 100 μL of H 2 O 2 DMEM medium (H 2 O 2 The final concentrations were 250, 500, 750, 1000, 1250, and 1500 μmol / L, respectively). After culturing the cells for 4 h, the cell viability was detected.

[0100] 25. Determination of ROS in Caco-2 cells

[0101] 3 × 10 4 Caco-2 cells were inoculated at a concentration of 100 μL / well and cultured for 48-72 h. After the cell density reached 90%, the culture medium was discarded and washed twice with PBS. 100 μL of DMEM growth medium was added to the cells in the blank control group and the induced model group, and 100 μL of free AST, Z / AST and Z / L / C / AST nanosphere solutions (the AST concentration in the control sample was 5 μM) and simulated digestion fluid (content was 15 μL / mL) were added to the sample treatment group for 4 h, and then the supernatant was discarded, washed twice with PBS, and 100 μL of 0.75 mM H 2 O 2 After 4 h of treatment with DMEM medium containing the solution, the cells were washed twice. 100 μL of DMEM growth medium was added to the cells in the blank control group and the induced model group, and the sample treatment group was treated with medium containing free AST, Z / AST, Z / L / C / AST nanosphere solution or simulated digestion solution for another 4 h.

[0102] DCFH-DA fluorescent dye was used to measure the level of intracellular ROS. The cells in the blank control group, model treatment group and sample treatment group were incubated with 10 μM DCFH-DA for 30 min in the dark. After removing the supernatant, the cells were washed 3 times with PBS to remove extracellular DCFH-DA, and the fluorescence of the cells in each well was immediately measured with a microplate reader. The excitation filter and emission filter were set to 485 nm and 525 nm, respectively.

[0103] 26. Determination of SOD, CAT and MDA in Caco-2 cells

[0104] In a 12-well plate, 1 × 10 5Inoculate Caco-2 cells at a concentration of 10 cells / well and continue culturing for 48-72 hours. After the cell density reaches 90%, discard the culture medium and wash twice with PBS. Treat the cells according to the method in 24 above, with 1 mL of culture medium per well.

[0105] The collected cells were ultrasonically disrupted (power 200 W, ultrasound 3 s, interval 10 s, total time 7 min), centrifuged at 4 ° C, 12000 × g for 15 min to obtain the upper extract, and then the SOD, CAT, and MDA contents of the cells were determined according to the method of the kit.

[0106] 27. Detection of HepG2 cell viability by CCK-8 method

[0107] The effects of Z / AST and Z / L / C / AST nanoparticles, simulated digestive fluid, and OA solution on the proliferation activity of HepG2 cells were determined using CCK-8 assay. 4 The cells / well were seeded in a 96-well plate and incubated at 37°C and 5% CO 2 The culture medium on the cell monolayer was discarded, and different concentrations of Z / L / AST and Z / L / C / AST nanosphere solutions, simulated digestive solution (the digestive solution is the micelle phase in the simulated gastrointestinal digestion dispersion) and OA solution were added to the HepG2 cell monolayer at a volume of 100 μL / well and incubated at 37°C with 5% CO 2 Cultured for 24 hours under induction. The concentrations of Z / L / AST and Z / L / C / AST nanospheres were 100, 200, 300, 400 and 500 μL / mL, the concentrations of simulated digestive fluid were 10, 20, 30, 40 and 50 μL / mL, and the experimental concentrations of OA were 0.125, 0.25, 0.5, 1 and 2 mM. After the culture, 10% CCK-8 reagent was added to each well and incubated at 37°C in the dark for 1 hour. The absorbance was then measured at 450 nm using an ELISA reader. Cell viability was calculated.

[0108] 28. Determination of lipid content in HepG2 cells

[0109] Based on the effects of free AST, Z / AST and Z / L / C / AST nanoparticles and simulated digestive fluid on the lipid levels of HepG2 cells, we investigated whether encapsulation had an effect on AST activity. 5HepG2 cells were inoculated at a concentration of 100 μg / mL cell / well. When the cell density reached 80%, the blank control group (CON) cells were treated with DMEM medium only, and the induced model group (MOD) and the sample treatment group were treated with 0.5 mM OA-BSA solution for 24 h. Subsequently, the sample treatment groups were added with free AST, Z / AST and Z / L / C / AST nanospheres (the AST concentration in the control sample was 10 μM) samples and simulated digestion fluid (content was 15 μL / mL) and cultured for 24 h. All cells were washed twice with cold PBS and then collected. The cells were lysed and centrifuged to obtain the supernatant. The TG, TC, HDL-C and LDL-C levels in HepG2 cells were determined according to the kit method.

[0110] 29. Cellular uptake of nanospheres

[0111] Absorption experiments were performed after Caco-2 cells formed a monolayer. 2 mL of free AST, Z / AST and Z / L / C / AST nanospheres diluted with DMEM and simulated digestion solution diluted with DMEM (the AST concentration in the control sample was consistent with 5 μM) were added to a 6-well plate. After incubation for 2 hours, the culture medium was discarded, the cells were washed with PBS and collected, the cells were broken and the broken cell fluid was extracted with a mixed organic reagent containing anhydrous ethanol / n-hexane (2:1, v / v). The extraction was repeated three times until the AST was completely extracted and then fixed to 5 mL with anhydrous ethanol. The absorbance was measured at 478 nm, and the AST content was calculated according to the AST standard curve.

[0112] The present invention is described below by means of illustrative specific examples, which are not intended to limit the scope of the present invention in any way. It is particularly noted that the reagents used in the present invention are commercially available unless otherwise specified.

[0113] Example 1 Preparation of Z / L / C / AST Nanospheres

[0114] Weigh 1.0g of zein and dissolve it in 100mL of 80% (v / v) ethanol solution, stir it magnetically at 500rpm for 1h, add soybean lecithin and stir it at 500rpm for 1h, then add astaxanthin (AST) and stir it at 500rpm for 10min, take 20mL and add it to 60mL of water to form a dispersion, stir the dispersion at 500rpm for 15min, remove the remaining ethanol in a rotary evaporator at 35℃, and finally centrifuge it at 730×g for 15min to remove large particles and insoluble AST. The dispersion is adjusted to pH 4.0 with HCl to obtain Z / L / AST nanospheres, which are then stored at 4℃ for use. Chitosan oligosaccharide (COS) was weighed to prepare a 10 mg / mL mother solution, 5 ml of Z / L / AST dispersion was added to 5 mL of COS solution, stirred at 500 rpm for 5 min, and the pH was adjusted to 4.0 with HCl to obtain Z / L / C / AST nanospheres, which were then stored at 4°C for use.

[0115] (1) Optimization of the mass ratio of Zein to Lecithin

[0116] Effect of Zein to Lecithin mass ratio on particle size, PDI and Zeta potential of composite nanoparticles Figure 2 As shown in the figure, the particle size of Z / AST nano-microspheres is 152nm. With the increase of Lecithin content, the particle size of Z / L / AST composite nano-microspheres shows a trend of first increasing, then decreasing and then increasing. When the mass ratio of Zein to Lecithin is 5:1, its particle size is 428nm, which is much larger than the particle size of Z / AST nano-microspheres, and the Zeta potential also drops significantly to 14.4mV, which is less than 20mV. When the mass ratio of Zein to Lecithin is 2:1, 3:2 and 1:1, its particle size shows a downward trend, which is 162nm, 142nm and 127nm respectively, which are significantly smaller than the Z / L / AST nano-microspheres with a mass ratio of 5:1. The PDI of all nano-microspheres is in the range of 0.05-0.70, indicating that they belong to a monodisperse system. Among them, the PDI of Z / AST nano-microspheres is 0.35. The change in PDI of Z / L / AST nanomicrospheres showed a trend of first decreasing and then increasing. When the mass ratio of Zein to Lecithin was 2:1, 3:2 and 1:1, the PDI of Z / L / AST nanomicrospheres were 0.12, 0.14 and 0.22, respectively, which were significantly lower than those of Z / AST nanomicrospheres (P<0.05).

[0117] The Zeta potential of Z / AST nanospheres is 43.2mV. When the ratio of Zein to Lecithin is 2:1, the surface charge of the nanospheres changes from positive to negative, indicating that the surface charge of Z / L / AST nanospheres changes from Zein-dominated to Lecithin-dominated. When the mass ratio of Zein to Lecithin is 2:3, the absolute value of its PDI and Zeta potential increases rapidly.

[0118] The embedding efficiency of Z / AST, L / AST and Z / L / AST nanoparticles is as follows Figure 3 As shown. In the absence of Lecithin, the embedding rate of Z / AST nanospheres was 71.3%, and the embedding rate of Z / L / AST nanospheres for AST gradually increased with the increase of Lecithin. When the mass ratio of Zein to Lecithin was 2:1, the embedding rate of Z / L / AST nanospheres was 97.1%, which was significantly higher than that of the composite nanospheres with a mass ratio of Zein to Lecithin of 5:1 (P<0.05), but significantly lower than the 99.6-99.8% of Z / L / AST nanospheres with a mass ratio of Zein to Lecithin of 3:2, 1:1, 2:3, 1:2 and 1:5 (P<0.05), and there was no significant difference in the embedding rate between the composite nanospheres with a mass ratio of Zein to Lecithin of 3:2, 1:1, 2:3, 1:2 and 1:5 (P<0.05). In the absence of Zein, the embedding rate of L / AST liposomes was 90.8%. This result indicates that Zein and Lecithin have a synergistic effect on improving the embedding efficiency of AST. Lecithin may promote the embedding of AST adhered to the surface of Zein or free AST in the composite nanospheres, and Lecithin can combine with AST to form a complex, thereby improving the embedding efficiency.

[0119] The results of AST retention rate after UV irradiation treatment of AST and Z / AST, L / AST and Z / L / AST nanoparticles are shown in Figure 4As shown. Compared with free AST, the retention rate of AST in Z / AST was significantly increased (P<0.05). After adding Lecithin, the retention rate of AST in Z / L / AST nanomicrospheres was further improved. After 60 minutes of UV treatment, there was no significant difference in the retention rate of AST in Z / L / AST nanomicrospheres with a Zein to Lecithin mass ratio of 1:1, 2:3 and 1:2, which decreased by 20.7%, 20.2% and 20.4%, respectively. However, after 120 minutes of UV treatment, the retention rate of AST in Z / L / AST nanomicrospheres with a Zein to Lecithin mass ratio of 2:3 and 1:2 decreased significantly, which decreased by 20.9% and 20.4%, respectively, compared with 60 minutes of UV treatment, and the Z / L / AST nanomicrospheres with a Zein to Lecithin mass ratio of 1:1 decreased by 16.6%. In summary, when the mass ratio of Zein to Lecithin is 1:1, the photostability of Z / L / AST nanoparticles to AST is optimal.

[0120] The effects of thermal processing on the stability of AST in nanoparticles were investigated by simulating pasteurization and high temperature treatment processes at 65°C for 30 min and 95°C for 15 min. Figure 5 As shown in the results, the retention rates of free AST were 49% and 28% under the conditions of 65℃, 30min and 95℃, 15min, respectively. With the addition of Zein or Lecithin, the retention rates of AST in Z / AST and L / AST were significantly increased (P<0.05). After treatment at 95℃ for 15min, the retention rates of AST in Z / AST and L / AST nanospheres were 71.7% and 72.0%, respectively. In addition, the protective effect of Z / L / AST nanospheres was more significant compared with that of Z / AST and L / AST nanospheres. When the mass ratio of Zein to Lecithin was 1:1, the retention rates of AST reached 92.0% and 91.2% after treatment at 65℃, 30min and 95℃, 15min, respectively. This may be because the presence of Lecithin made the Z / L / AST nanospheres form a more compact structure, thereby improving the retention rate of AST during heat treatment. After treatment at 95℃ for 15min, the retention rate of AST in Z / L / AST nanoparticles with Zein to Lecithin mass ratios of 3:2, 1:1, and 2:3 was higher than that in other Z / L / AST groups. This may be because the Z / L / AST nanoparticles (Zein to Lecithin mass ratios of 3:2, 1:1, and 2:3) had smaller particle sizes and more uniform particle size distribution, resulting in a smaller surface area and reduced contact with environmental stress.

[0121] In summary, combined with the results of particle size, PDI, Zeta potential, embedding rate, photostability and temperature stability, when the mass ratio of Zein to Lecithin is 1:1, Z / L / AST nanoparticles have the smallest particle size (average particle size = 127nm), smaller particle size distribution (PDI = 0.22), larger Zeta-potential (|-43.5mV|>20mV), higher embedding rate (99.6%), optimal photostability and best temperature stability. In the future, the mass ratio of Zein to Lecithin will be selected as 1:1 as the preparation parameter for preparing Z / L / AST nanoparticles.

[0122] (2) Optimization of COS addition amount

[0123] The mass ratio of Lecithin to COS was used as the optimization parameter for preparing Z / L / C / AST nanoparticles. The effect of the addition ratio of Lecithin to COS on the particle size, PDI and Zeta potential of the nanoparticles is shown in Figure 2. Figure 6 As shown in A. The size of Z / L / C / AST nano-microspheres changes significantly with the change of the mass ratio of Lecithin to COS. With the increase of COS content, the particle size of Z / L / C / AST nano-microspheres increases first, then decreases, and then increases again. When the mass ratio of Lecithin to COS is 5:1, its particle size is 193nm, which is significantly larger than the particle size of Z / L / AST nano-microspheres (the mass ratio of Zein to Lecithin is 1:1). With the increase of COS content, the particle size of Z / L / C / AST nano-microspheres begins to decrease. When the mass ratio of Lecithin to COS is 2:1, its particle size is 141nm, which is significantly smaller than the Z / L / C / AST nano-microspheres with the mass ratio of Lecithin to COS of 5:1, 4:1 and 3:1 (P<0.05). As the COS content continues to increase, its particle size continues to increase. The effect of the mass ratio of lecithin to COS on the PDI of Z / L / C / AST nanoparticles is consistent with the trend of particle size change. The PDI of Z / L / C / AST nanoparticles with a mass ratio of lecithin to COS of 2:1 is significantly lower than that of other Z / L / C / AST nanoparticles with COS added.

[0124] Effect of Lecithin to COS mass ratio on the Zeta potential of Z / L / C / AST nanoparticles Figure 6As shown in B. With the increase of COS content, the Zeta potential of Z / L / C / AST composite nanospheres showed an increasing trend. The potential of Z / L / C / AST nanospheres with a mass ratio of Lecithin to COS of 5:1, 4:1 and 3:1 gradually increased, but its absolute value was less than 20mV. The trend of increasing Zeta potential corresponds to the trend of decreasing particle size and PDI, indicating that the increase in the absolute value of Zeta potential is conducive to the formation of smaller and more uniform nanospheres in the dispersed system. There was no significant difference in the Zeta potential of Z / L / C / AST nanospheres with a mass ratio of Lecithin to COS of 2:1, 1:1 and 1:2 (P>0.05).

[0125] The embedding efficiency of Z / L / C / AST nanoparticles is as follows Figure 7 As shown. Compared with Z / L / AST (Zein and Lecithin mass ratio is 1:1) nanospheres without COS, the embedding rate of Z / L / C / AST nanospheres with COS added was significantly increased (P<0.05). There was no significant difference in the embedding rate between Z / L / C / AST nanospheres with different COS contents (P>0.05) and the embedding rates were all greater than 99.0%, indicating that the addition of COS did not have an adverse effect on the embedding rate of Z / L / C / AST nanospheres.

[0126] The results of UV irradiation treatment of AST, Z / L / AST (Zein and Lecithin mass ratio is 1:1) nanoparticles and Z / L / C / AST nanoparticles are shown in Figure 8As shown. The stability of AST in Z / L / C / AST nanospheres under ultraviolet light was significantly improved compared with free AST (P<0.05). With the addition of COS, the retention rate of AST in Z / L / C / AST nanospheres under ultraviolet light showed a trend of first decreasing and then increasing. When the mass ratio of Lecithin to COS was 5:1, the retention rates of AST in the nanospheres after ultraviolet light treatment for 60min and 120min were 73.0% and 53.1%, respectively, which were significantly decreased compared with Z / L / AST (the mass ratio of Zein to Lecithin was 1:1) nanospheres (P<0.05). This may be because a small amount of COS destroyed the stability of Z / L / AST nanospheres, resulting in a larger particle size and particle size distribution and a smaller absolute value of Zeta potential, making the system unstable and reducing the ultraviolet protection of nanospheres on AST. With the increase of COS content, the ultraviolet protection of Z / L / C / AST nanospheres on AST was significantly enhanced (P<0.05). After UV treatment for 60min and 120min, the retention rates of AST in Z / L / C / AST nanomicrospheres with a mass ratio of Lecithin to COS of 1:2 were 89.4% and 75.2%, respectively, which were significantly higher than those of Z / L / AST (mass ratio of Zein to Lecithin was 1:1) nanomicrospheres (77.5% and 59.3%) (P<0.05).

[0127] Effects of different temperature treatments on AST and Z / L / C / AST nanoparticles with different Lecithin to COS mass ratios Fig. 9 As shown. The retention rate of AST in Z / L / C / AST nanomicrospheres showed a trend of first decreasing and then increasing with the increase of COS content. After treatment at 65℃, 30min and 95℃, 15min, the retention rates of AST in Z / L / C / AST nanomicrospheres with a mass ratio of Lecithin to COS of 2:1 were 94.4% and 92.5%, respectively, which were higher than those of Z / L / AST nanomicrospheres (mass ratio of Zein to Lecithin was 1:1). This shows that the introduction of COS enhances the temperature protection effect of Z / L / AST composite nanomicrospheres on AST. In addition, the effect of temperature treatment on the retention rate of AST in Z / L / C / AST nanomicrospheres is similar to the particle size trend of Z / L / C / AST nanomicrospheres. The larger the particle size, the lower the retention rate of AST. In summary, a mass ratio of Lecithin to COS of 2:1 was selected as the preparation parameter for preparing Z / L / AST nanomicrospheres.

[0128] Example 2: Embedding mechanism and stability of Z / L / C / AST nanoparticles

[0129] Weigh 1.0g Zein and dissolve it in 100mL 80% (v / v) ethanol solution. Stir magnetically at 500rpm for 1h, add 1.0g Lecithin and stir for 1h, then add AST, stir at 500rpm for 10min, take 20mL and add it to 60mL water to form a dispersion. After the dispersion is stirred at 500rpm for 15min, remove the remaining ethanol in a rotary evaporator at 35℃, and finally centrifuge at 730×g for 15min to remove large particles and insoluble AST. The pH of the Z / L / AST dispersion is adjusted to 4.0 with HCl. Then take 5ml of the Z / L / AST dispersion and add it to the 5Ml COS diluted solution so that the mass ratio of Lecithin to COS is 2:1. Stir at 500rpm for 5min and adjust the pH to 4.0 with HCl.

[0130] (1) Structural characterization of nanospheres

[0131] The UV spectra of AST solution and Z / L / C / AST nanosphere extract were scanned in the range of 400nm-700nm. The results are as follows: Fig.10 As shown, the UV absorption peaks of AST solution and Z / L / C / AST nanosphere extract are similar and both have maximum absorption peaks at 478 nm, indicating that the AST after embedding has not undergone chemical changes and its properties remain unchanged.

[0132] The crystallinity of AST, Zein, Lecithin, Z / L and Z / L / C nanospheres, as well as Z / L / AST and Z / L / C / AST nanospheres was determined by X-ray diffractometer. Fig.11 As shown. The main characteristic peaks of AST appear at 10.9, 14.1, 16.2, 18.2, 20.4 and 24.8°, indicating that it has a highly crystalline nature. Zein has two broad peaks instead of sharp peaks at diffraction angles 2θ of 9.1° and 19.2°, COS has only one flat broad peak, and Lecithin has a broad peak at 19.3°, all of which indicate the amorphous nature of Zein, COS and Lecithin. Fig.11 It can be seen that the characteristic crystal peak of AST does not appear in the X-ray diffraction patterns of Z / L / AST and Z / L / C / AST nanospheres. The disappearance of the characteristic peak of AST indicates that AST exists in an amorphous state in the nanospheres, and further proves that AST is successfully embedded in the nanoparticles.

[0133] Differential scanning calorimetry spectra of different nanospheres and AST are shown in Figure 2. Fig.12 As shown. Fig.12As shown in Figure A, AST shows an obvious characteristic endothermic peak at around 222°C, which is attributed to the melting of AST crystals, indicating that AST exists in a crystalline state. Fig.12 As shown in Figure B, the characteristic endothermic peak of crystalline AST was not observed in Z / AST, Z / L / AST and Z / / L / C / AST nanospheres, indicating that AST was dispersed in the nanospheres in an amorphous form. These results are consistent with the results of XRD analysis, indicating that AST formed an amorphous complex with Zein and Lecithin. Unlike crystalline AST, the dissolution and diffusion of amorphous AST requires less energy, making it more soluble. The endothermic peak of Z / AST nanospheres appears at around 89°C. The denaturation temperature of the nanospheres increased to 98°C and 134°C with the addition of Lecithin and COS, respectively, indicating that the presence of Lecithin and COS may enhance the hydrophobic effect, electrostatic interaction and other interactions between different components in the nanospheres, resulting in a higher temperature absorption peak and improving the thermal stability of the nanospheres.

[0134] Fig.13 The transmission electron microscope image of Z / L / C / AST nanospheres. It can be seen from the figure that Z / L / C / AST nanospheres present a relatively regular spherical shape. The nanospheres were dyed with phosphotungstic acid and the shell layer on the surface of the nanospheres was dyed black, indicating that the AST-loaded zein / phosphatidylcholine / chitosan oligosaccharide microsphere carrier was successfully constructed and presented a core-shell structure.

[0135] (2) Ultraviolet absorption spectrum analysis

[0136] Depend on Fig.14 It can be seen that there is an absorption peak at around 280nm, which is the characteristic absorption peak of the C=O main chain structure or conjugated double bond of aromatic amino acids (tyrosine, phenylalanine and tryptophan) residues. In addition, the introduction of AST leads to an increase in the absorbance of Zein, indicating that AST affects the ultraviolet absorption of Zein, and the ultraviolet absorption intensity of Zein increases with the increase of AST molecular concentration.

[0137] (3) Intrinsic fluorescence spectroscopy analysis

[0138] like Fig.15As shown, when the excitation wavelength is 280nm, at 298K, Zein and Zein-Lecithin have strong fluorescence emission peaks at 306nm and 305nm, respectively. This is because the chromophore tyrosine produces strong fluorescence under the excitation of light with a wavelength of 280nm. At 298K, after adding 21μM AST, the fluorescence intensity decreased by 51.7% and 50.6%, respectively, indicating that the intrinsic fluorescence of Zein and Zein-Lecithin was quenched. AST can quench the intrinsic fluorescence of Zein and Zein-Lecithin in a concentration-dependent manner, and the fluorescence emission peak is slightly shifted. The above results show that AST interacts with the mixed system of Zein and Zein-Lecithin, inhibiting the fluorescence intensity of the chromophore.

[0139] (4) Analysis of fluorescence quenching mechanism

[0140] Fluorescence quenching can be divided into two different categories: static quenching and dynamic quenching. Both quenching processes can be explained by the Sterne-Volmer equation and distinguished by their different temperature dependencies, bimolecular quenching rate constants, and absorption spectra. The Stern-Volmer equation is as follows:

[0141] F 0 / F=1+K q τ 0 [Q]=1+K sv [Q]

[0142] In the formula, F and F 0 represents the fluorescence intensity of the fluorophore molecule (Zein) in the presence and absence of the quencher molecule (AST); [Q] is the concentration of the quencher AST; K sv is the Stern-Volmer quenching constant; τ 0 (10 -8 s) represents the average fluorescence lifetime of Zein in the absence of a quencher; and K q is the quenching rate constant.

[0143] The Stern-Volmer curves of the interaction between AST and Zein and Zein-Lecithin are shown in Figure 2. Fig.16 As shown, the curve has a good linear relationship, indicating that the interaction between AST and Zein and Zein-Lecithin only follows static or dynamic quenching. The fluorescence quenching constants of the interaction between AST and Zein and Zein-Lecithin are shown in Table 1. Among them, the K constants of Zein and AST at 298, 304, and 310 K are q 5.41×1012 , 5.38×10 12 5.28×10 12 M -1 ·s -1 , K of Zein-Lecithin and AST at three temperatures q 5.06×10 12 4.99×10 12 4.92×10 12 M -1 ·s -1 The maximum dynamic quenching rate constant is reported to be 2×10 10 M -1 ·s -1 . Zein and AST's K q and K of Zein-Lecithin and AST q All above 2×10 10 M -1 ·s -1 , which shows that the quenching process of AST on Zein and Zein-Lecithin mixed system follows static quenching. In the quenching process of AST on Zein and Zein-Lecithin mixed system, K sv The decrease of the value with the increase of temperature also confirms the conclusion that the interaction between AST and Zein and Zein-Lecithin mixed system follows static quenching. In addition, Lecithin does not change the quenching mechanism of AST on Zein.

[0144] Table 1 Fluorescence quenching constants

[0145]

[0146] (5) Analysis of binding constant and number of binding sites

[0147] For the static quenching process, the number of binding sites (n) and the binding constant (K) were calculated using the following formula: a ):

[0148]

[0149] Among them, F and F 0 represent the fluorescence intensity of the fluorophore molecule (Zein) in the presence and absence of the quencher molecule (AST); [Q] is the concentration of the quencher AST, K a represents the binding constant and n represents the number of binding sites.

[0150] like Fig.17As shown in the figure, the double logarithmic curves of the interaction between AST and Zein and Zein-Lecithin mixed systems have good linearity, indicating that the K calculated according to the above formula is a The binding constants and binding sites of AST with Zein and Zein-Lecithin are shown in Table 2. The K values ​​in the AST-Zein and AST-Zein-Lecithin mixed systems are a The values ​​are 6.27, 2.90, and 1.30×10 5 M -1 and 7.63, 3.35, 1.88×10 5 M -1 . Studies have reported several other carotenoids interacting with proteins a Value is 10 3 -10 4 M -1 In the AST-Zein and AST-Zein-Lecithin mixed systems, K a The values ​​are all larger than this range, which indicates that AST can form a more stable combination with Zein and Zein-Lecithin in the AST-Zein and AST-Zein-Lecithin mixed systems.

[0151] At the same time, the n value in the AST-Zein and AST-Zein-Lecithin mixed systems decreases with increasing temperature, and the n value is about 1. Based on this result, it can be judged that there is a binding site between AST and Zein and Zein-Lecithin. In addition, the AST-Zein-Lecithin complex has a larger K compared with the AST-Zein complex. a The value indicates that after adding Lecithin, the interaction between AST and Zein-Lecithin complex is stronger, and a more stable complex can be formed.

[0152] Table 2 Binding constants and binding sites

[0153]

[0154] (6) Binding force analysis

[0155] Thermodynamic parameters can be calculated according to the following Van't Hoff equation:

[0156] LqCy a =-ΔH / RT+ΔS / R

[0157] ΔG=ΔH-TΔS=-RTInK a

[0158] Where K a represents the binding constant; R represents the gas state constant; T is the absolute temperature of the experiment (K).

[0159] like Fig.18 The thermodynamic parameters of the interaction between AST and Zein and Zein-Lecithin are shown in Table 3. When AST interacts with Zein and Zein-Lecithin mixed systems, its ΔG is less than zero, which indicates that the binding between AST and Zein and Zein-Lecithin is a spontaneous process. In addition, the ΔH value and ΔS value are both less than zero, which also indicates that the binding process between AST and Zein and Zein-Lecithin mainly involves hydrogen bonds and van der Waals forces.

[0160] Table 3 Thermodynamic parameters

[0161]

[0162]

[0163] (7) Molecular docking analysis

[0164] Molecular docking of AST-Zein-Lecithin composite system Fig.19 As shown. The best conformation with the lowest free energy was selected for further analysis. The negative value of ΔG of -7.80 kcal / mol indicates that AST and can spontaneously bind to Zein. Among them, the ΔG of the binding of Lecithin to Zein is -5.87 kcal / mol, indicating that Lecithin also has a strong binding effect with Zein.

[0165] Depend on Fig.19 It can be seen that both AST and Lecithin are embedded in the cavity of Zein and interact with many amino acid residues. Fig.19 From B and C, it can be seen that the oxygen atom on the ionone ring in AST forms a hydrogen bond with the hydrogen atom of the Gln108 residue of Zein, and the Gln101, Gln106, Gln151, Gln144, Asn94, Asn123, Thr111, Ala112, Pro130 and Leu90 residues of Zein around AST participate in the binding of Zein and AST through van der Waals forces. Other residues Phe119, Leu93, Leu104, Leu136, Ala126, Ala127 and Tyr133 form a hydrophobic pocket that wraps the AST molecule. Fig.19As can be seen from D and E, the Ser190, Thr152, and Gln193 residues of Zein participate in the binding of Zein and Lecithin through hydrogen bonds, the Leu156, Leu176, Leu174, Leu200, Val180, Gln155, Gln172, Aln183, Ile196, Rhe179, Rhe201, Pro194, Gly197, ​​and Thr169 residues form van der Waals forces with Lecithin, and there are hydrophobic interactions between the residues Pro158, Phe159, Leu173, and Phe163 of Zein and Lecithin.

[0166] The molecular docking results show that the binding of AST to Zein is mainly dominated by hydrogen bonds and van der Waals forces, which is consistent with the result that the ΔH value and ΔS value in the thermodynamic parameters are both less than zero. At the same time, the hydrophobic interaction is also an important force between AST and Zein. Finally, the binding energy between AST and Zein is lower than that between Lecithin and Zein, and there is a strong hydrophobic interaction when AST binds to Zein, indicating that AST is more easily bound to the hydrophobic cavity of Zein.

[0167] (8) Effect of reactive additives

[0168] Effects of urea, SDS and NaCl on the turbidity of Zein-Lecithin and Lecithin-COS complexes Fig. 20 As shown. The turbidity of Zein-Lecithin and Lecithin-COS complexes decreased significantly after the addition of urea or SDS, but increased after the addition of NaCl. These results indicate that the interaction between Zein and Lecithin is mainly driven by a combination of hydrogen bonding and hydrophobic interactions. Among them, the turbidity of the Lecithin-COS complex increased significantly after the addition of NaCl, indicating that electrostatic interaction is an important role mode of interaction between Lecithin and COS.

[0169] (9) Fourier transform infrared spectroscopy analysis

[0170] like Fig.21 As shown, Zein at 3312cm -1 There is an obvious absorption peak near the -OH group. When AST and Lecithin coexist, the peak positions of Z / AST, Z / L, and Z / L / AST hydrogen bonds shift to 3301, 3302, and 3302 cm -1 This indicates that there is a hydrogen bond between Zein, Lecithin and AST. The typical absorption peaks of Zein (amide I and amide II) appear at 1659 and 1539 cm -1The amide I band is related to C=O stretching, and the absorption peak of amide II is due to CNH in-plane bending, CN and CC stretching. Compared with Zein, the amide I and amide II bands of Z / AST nanospheres shift from 1659 to 1539 cm -1 Move to 1650 and 1530cm -1 , indicating that there is an electrostatic interaction between Zein and AST. Zein contains many hydrophobic amino acids (about 75%), which may have hydrophobic interactions with the hydrophobic AST molecules. In Z / L / AST nanospheres, the bands of amide I and amide II groups are at 1659 and 1539 cm -1 Move to 1654 and 1546cm -1 , indicating that there is an electrostatic interaction between Zein, Lecithin and AST.

[0171] COS at 1624cm -1 The stretching of C=O of amide I is shown in Figure 2. Compared with COS, the bands of amide I and amide II groups in Z / L / C and Z / L / C / AST nanospheres shift from 1624 to 1412 cm -1 Move to 1657, 1535cm -1 and 1454, 1456, indicating that there is a strong electrostatic interaction between COS and Lecithin. In addition, COS was observed at 3385 cm -1 The peak at 3307 cm-1 corresponds to the -OH group, and the peak positions of hydrogen bonds of Z / L / C and Z / L / C / AST nanospheres shift to 3307 cm-1 and 3308 cm-1. -1 The results showed that hydrogen bonding occurred among Zein, Lecithin and COS.

[0172] Lecithin at 1743 and 1235cm -1 The strong peak at 3497 cm is caused by the stretching vibration of C=O and P=O. -1 There is a sharp peak at 1551 and 1651 cm -1 The characteristic peaks near the AST molecular structure represent the C=C and C=O stretching vibrations in the violet copper ring, and the CH bending of the conjugated CC bond is located at 976 cm -1 Most of the characteristic peaks of AST are 1551, 1651 and 976 cm -1 It disappeared in the Z / AST, L / AST, Z / L / AST and Z / L / C / AST spectra, indicating that AST was encapsulated in the Z / AST, L / A / ST, Z / L / A / ST and Z / L / C / A / ST nanospheres.

[0173] (10) Schematic diagram of nano-microsphere binding

[0174] like Fig. 22 As shown. Fig. 22 As shown in Figure A, Zein can spontaneously form spherical nanoparticles. In the Z / AST nanoparticles, AST is bound to the helical structure of Zein, and a small amount of free AST is not embedded in the Z / AST nanoparticles. Fig. 22 As shown in Figure B, after adding Lecithin, the surface of Z / L / AST nanoparticles was covered by Lecithin molecules, and the free AST was encapsulated in the hydrophobic end of Lecithin, which is one of the reasons for the improvement of the encapsulation rate of Z / L / AST nanoparticles.

[0175] Subsequently, the positively charged COS binds to the Lecithin on the surface of the Z / L / AST nanospheres through electrostatic bonding to form a shell structure.

[0176] (11) Photodegradation kinetics analysis

[0177] In most cases, the photodegradation of AST in the delivery system follows first-order kinetics, which is manifested as a decrease in the total apparent concentration of AST in the delivery system. Fig.23 Shown is a logarithmic plot of AST concentration normalized to the initial value at t=0 (t=time). The kinetic constants can be obtained from the slopes of the linear adjustments and the resulting relevant values ​​are shown in Table 4.

[0178] Depend on Fig.23 It can be seen that all nanosystems have a good degree of fit in the first-order kinetic equation. The nanosystem can protect AST from photodegradation under ultraviolet light. The larger the degradation kinetic constant of the active substance, the faster its degradation rate. Under ultraviolet light irradiation conditions, the degradation rate of free AST is the fastest, and its degradation kinetic constant is 0.0285 (min-1), which is 4.5, 7.5 and 13.0 times that of the Z / AST, Z / L / AST and Z / L / C / AST nanosystems, respectively. The Z / L / C / AST nanosystem has the smallest degradation kinetic constant and the smallest degradation rate. The above results show that the degradation of free AST and AST in the Z / AST, Z / L / AST and Z / L / C / AST nanosystems conforms to the first-order kinetic equation, and the nanosystem can effectively protect AST from photodegradation.

[0179] Table 4 Kinetic constants of photodegradation of AST in different nanosystems; R 2 yes Fig.23 The linear regression coefficient of the curve shown is

[0180]

[0181] (12) Storage degradation kinetics analysis

[0182] The effect of encapsulation on the storage stability of AST was investigated by studying the degradation kinetics of AST in different nanosystems stored in the dark at 4°C and 25°C for 28 days.

[0183] The degradation of AST conforms to the first-order reaction kinetics equation, which can be used to analyze the degradation rate constant and half-life of AST. The first-order reaction kinetics equation is as follows:

[0184] ln(c / c 0 )=-kt

[0185]

[0186] Where k is the degradation rate constant (d -1 ), t 1 / 2 is the half-life (d), C 0 is the initial AST concentration of the nanospheres, C is the AST concentration of the nanospheres at day t, and t is the storage time (d).

[0187] The ln(c / c of ​​free AST and different nanosystems stored at 4℃ and 25℃ 0 The relationship between ) and t is shown in the figure Fig.24 A and Fig.24 As shown in B.

[0188] The degradation kinetics of AST after storage at different temperatures (4°C and 25°C) and in the dark for different days were studied. Fig.24 As shown, the horizontal axis is the storage time, and the vertical axis is the ln (c / c 0 It can be clearly seen that the ln(c / c 0 ) showed a good linear relationship with the storage days, which indicated that the degradation and storage process of free AST, Z / AST, Z / L / AST, and Z / L / C / AST conformed to the first-order kinetic equation.

[0189] In addition, according to the first-order reaction kinetic equation and Fig.24 The rate constant k and half-life t of AST-DMSO, Z / AST, Z / L / AST, and Z / L / C / AST can be calculated. 1 / 2The calculation results are listed in Table 5. It can be observed that under two different storage conditions (4°C and 25°C), the k values ​​of Z / AST, Z / L / AST, and Z / L / C / AST nanosystems are lower than the k value of free AST (AST-DMSO). The smaller the k value, the slower the degradation rate, which indicates that the degradation rate of Z / AST, Z / L / AST, and Z / L / C / AST is slower. In addition, under the storage condition of 4°C, the t 1 / 2 Much shorter than Z / AST, Z / L / AST, and Z / L / C / AST. The half-lives of Z / AST, Z / L / AST, and Z / L / C / AST are respectively shorter than the t 1 / 2 (41.0d) increased by 2.6, 5.3 and 6.1 times. Under 4℃ storage conditions, the t 1 / 2 Much shorter than Z / AST, Z / L / AST, and Z / L / C / AST. The half-lives of Z / AST, Z / L / AST, and Z / L / C / AST are respectively shorter than the t 1 / 2 (25.2d) increased by 1.8 times, 4.2 times and 5.1 times. The above results show that the introduction of Lecithin and COS improves the storage stability of Z / AST nanosystem.

[0190] Table 5 Degradation kinetics of AST in different nanosystems stored at 4℃ and 25℃ for 28 days

[0191]

[0192] Example 3 Effects of Z / L / C / AST nanoparticles on AST digestion, absorption, antioxidant and lipid-lowering activity

[0193] (1) Analysis of AST retention rate: Results of AST retention rate after simulated gastric digestion and simulated intestinal digestion using nanoparticles Fig.25As shown. The results showed that AST in the nanoparticles was lost after simulated gastrointestinal digestion. After simulated gastric digestion, the loss rate of unencapsulated AST reached 56.0%, while the loss rates of AST encapsulated by Zein and Zein-Lecithin, Zein-Lecithin-COS complexes were all within 20.0%. After the subsequent simulated intestinal digestion, the retention rate of unencapsulated AST was only 37.6%, while the retention rates of AST encapsulated by Zein and Zein-Lecithin, Zein-Lecithin-COS complexes were all above 70.0%. In addition, after simulated gastrointestinal digestion, the retention rates of AST in Z / L / AST and Z / L / C / AST nanoparticles were significantly increased compared with those in Z / AST nanoparticles (P<0.05), and the retention rates were increased by 6.2% and 12.5%, respectively. The results show that encapsulation of AST by Zein and Zein-Lecithin, Zein-Lecithin-COS can protect AST in simulated gastrointestinal digestion. In addition, compared with Zein and Zein-Lecithin, Zein-Lecithin-COS complex has a better protective effect on AST in simulated gastrointestinal digestion, and the protective ability is further improved after the introduction of COS.

[0194] (2) Analysis of AST bioavailability: The bioavailability of free AST and AST encapsulated by Zein, Zein-Lecithin, and Zein-Lecithin-COS complexes after simulated gastrointestinal digestion was determined. Fig.26 As shown. The bioavailability of free AST is low, only 3.9%. The bioavailability of AST encapsulated by Zein, Zein-Lecithin, and Zein-Lecithin-COS complexes after simulated gastrointestinal digestion was significantly improved (P<0.05), increasing by 8.1 times, 17.6 times, and 17.0 times, respectively. In addition, the bioavailability of AST encapsulated by Zein is much lower than that of AST encapsulated by Zein-Lecithin and Zein-Lecithin-COS complexes, indicating that hydrophobic bioactive substances may have difficulty entering the water-based environment of the gastrointestinal tract under oil-free conditions. The above results indicate that the introduction of Lecithin improves the bioavailability of AST in nanospheres.

[0195] (3) Absorption of AST in nanoparticles by Caco-2 cells: The absorption of AST in Z / AST and Z / L / C / AST nanoparticles by Caco-2 cells before and after simulated digestion was as follows: Fig. 27As shown. Studies have shown that smaller particle sizes of nanospheres are often more conducive to cell absorption. However, the absorption efficiency of bioactive substances in Z / AST nanospheres is significantly lower than that of Z / L / C / AST nanospheres. The possible reason is that Z / AST has a smaller particle size, but a larger PDI, uneven particle size, and particles with larger particle sizes, which inhibit the cell absorption efficiency of Z / AST nanospheres. In addition, slight aggregation of Z / AST nanospheres in the culture medium was observed in the absorption experiment. The environmental pH of the cell culture medium is around 7, which is close to the isoelectric point of Zein (pI=6.2). When Z / AST nanospheres are added to the cell culture medium, the environmental pH of Z / AST nanospheres will rise from 4 to about 7. When passing the isoelectric point of Zein, the surface charge intensity of Z / AST nanospheres drops sharply, resulting in bridging aggregation of nanoparticles, thereby reducing the cell absorption efficiency of Z / AST nanospheres.

[0196] After simulated gastrointestinal digestion, the cellular absorption efficiency of fat-soluble bioactive substances in the nanomicrospheres was significantly improved. Specifically, after simulated digestion, the cellular uptake of AST in Z / AST and Z / L / C / AST nanomicrospheres increased by 2.8 times and 0.7 times, respectively, compared with before digestion. This result clearly shows that the simulated digestion process promotes the release of AST from the nanomicrospheres and its absorption by cells. In addition, the cellular absorption efficiency of the Z / L / C / AST digested samples was higher than that of the Z / AST digested samples, which is consistent with the trend before simulated digestion. This further emphasizes the positive role of the addition of Lecithin and COS in enhancing the cellular absorption efficiency of AST.

[0197] (4) Scavenging effect of nanoparticles on ABTS free radicals: Z / AST, Z / L / C, Z / L / C / AST nanoparticles and free AST on ABTS + Cleansing effect Fig.28 As shown in the figure, AST is a substance with extremely strong antioxidant activity, but free AST is lower in all experimental concentrations. + AST is a fat-soluble bioactive substance. Its low solubility in water limits its biological activity. It is similar to ABTS in water environment. + The low contact amount is an important reason affecting its biological activity. At 20μM AST concentration, the ABTS· +The scavenging activities were 27.6%, 22.2%, 38.0% and 7.3% respectively. In addition, Z / L / C nanoparticles also showed strong antioxidant activity because COS, as a small molecule oligosaccharide of chitosan, also has certain antioxidant biological activity. At 20μM AST concentration, Z / L / C / AST nanoparticles and Z / L / C nanoparticles showed strong antioxidant activity against ABTS· + The difference in clearance rate was 15.8%, which was higher than the 7.3% of free AST, but lower than the 27.6% of Z / AST nanoparticles. This result shows that after Zein-Lecithin-COS encapsulated AST, its ABTS· + The enhanced scavenging effect may be due to the fact that after AST was embedded, the nanoparticles increased the water solubility and increased the specific surface area, increasing the affinity with ABTS· + The contact amount, thereby increasing the ABTS of AST + The difference in clearance between Z / L / C / AST nanospheres and Z / L / C nanospheres was lower than that of Z / AST nanospheres. This may be because the Zein-Lecithin-COS complex encapsulated AST nanospheres to form a more stable structure than the pure Zein encapsulated AST nanospheres, which slowed down its release rate in water and temporarily reduced the ABTS of AST in the nanospheres. + This result indicates that the nanospheres formed by Zein-Lecithin-COS complex may be more stable than those formed by pure Zein.

[0198] (5) Scavenging effect of nanoparticles on DPPH free radicals: The scavenging effect of Z / AST, Z / L / C, Z / L / C / AST nanoparticles and free AST on DPPH free radicals is as follows: Fig.29 As shown in the figure, free AST still showed a low free radical scavenging effect at all experimental concentrations, but at an AST concentration of 5 μM, there was no significant difference between free astaxanthin and Z / L / C nanoparticles. As the AST concentration increased, the DPPH of free AST and Z / AST, Z / L / C, and Z / L / C / AST nanoparticles increased. · There was a significant difference in the scavenging effect of Z / AST, Z / L / C, Z / L / C / AST nanoparticles and free AST on DPPH· at a concentration of 20 μM. This may be because the ethanol content in the experimental system remained unchanged, while the solubility of free AST in ethanol was still low. Increasing the AST content did not significantly increase the dissolved AST content in the experimental system, so the scavenging effect of free AST on DPPH· was still at a low level. ·The scavenging activities were 39.1%, 31.8%, 58.5% and 22.9% respectively. The difference in scavenging rate of DPPH· between Z / L / C / AST nanospheres and Z / L / C nanospheres was compared with the scavenging rate of free AST and Z / AST, which was similar to the above-mentioned situation of nanospheres scavenging ABTS free radicals. The results of scavenging effect of nanospheres on ABTS free radicals and DPPH free radicals showed that AST encapsulated in nanospheres can improve the antioxidant activity of AST in a water-based environment.

[0199] (6) Antioxidant capacity of in vitro simulated digestion products of nanoparticles: The antioxidant activity results of in vitro simulated digestion products of free AST, Z / AST and Z / L / C / AST nanoparticles are as follows: Fig.30 As shown. Among them, the ABTS free radical scavenging ability of free AST, Z / AST and Z / L / C / AST nanoparticles decreased from 7.3%, 27.6% and 38.0% before digestion to 7.0%, 16.9% and 32.0%, respectively, down by 4.1%, 38.8% and 15.8%, respectively. The DPPH free radical scavenging ability decreased from 22.9%, 39.1% and 58.5% before digestion to 14.8%, 16.5% and 40.1%, respectively. They decreased by 35.4%, 57.8% and 31.5%, respectively. The results showed that the percentage of ABTS free radical scavenging ability of free AST decreased the least after simulated gastrointestinal digestion. This result shows that simulated gastrointestinal digestion has improved the ABTS free radical scavenging ability of free AST to a certain extent, but the percentage of DPPH free radical scavenging ability has returned to a higher level, which may be because the solubility of free AST and AST in the simulated gastrointestinal digestion products in the DPPH system is similar. In addition, the antioxidant activity of free AST was always lower than that of AST encapsulated in nanospheres, which indicated that nanospheres could effectively enhance the antioxidant activity of free AST.

[0200] (7) Nanoparticles and their simulated digestive fluid and H 2 O 2 Effect of different concentrations of Z / AST and Z / L / C / AST nanosphere delivery systems and their simulated digestive fluids as well as different concentrations of H 2 O 2 Effects on Caco-2 cell viability Fig.31 As shown. Fig.31 As shown in A and B, the Z / AST and Z / L / C / AST nanosphere delivery systems did not cause cytotoxicity to Caco-2 cells (cell viability > 90%) at a concentration of 0-500 μL / mL, indicating that the prepared Z / AST and Z / L / C / AST nanosphere delivery systems had good biocompatibility.

[0201] Fig.31 C shows that different concentrations of H 2 O 2 After treating Caco-2 cells for 4 h, the viability of Caco-2 cells decreased significantly, indicating that oxidative damage can be induced in Caco-2 cells within the experimental concentration range (250-1500 μM). 2 O 2 When the concentration was 750 μM, the cell viability was close to 50%. 2 O 2 The concentration of 750 μM was used as the induction condition for the Caco-2 cell oxidative damage model.

[0202] Fig.31 Data D and E show that the cytotoxicity of the samples increased after the nanospheres were digested in the gastrointestinal tract. When the concentration of the digestive fluid reached 50 μL / mL, the cell viability of the simulated digestion products of the Z / AST and Z / L / C / AST nanosphere delivery systems was less than 50%, indicating that simulated gastrointestinal digestion can induce cytotoxicity.

[0203] (8) Effects of nanoparticles on ROS in Caco-2 cells damaged by oxidation: Effects of free AST, nanoparticles, and their digestion products on ROS content in Caco-2 cells. Fig.32 Compared with the CON group, the 2 O 2 The ROS content in the MOD group treated with AST increased significantly (P<0.01). Compared with the MOD group, the ROS level in the cells treated with free AST decreased significantly (P<0.05), which was inconsistent with the results of the extremely low absorption effect of free AST in the cell absorption experiment. The possible reason is that after the free AST was added for pre-protection in the experiment, it was difficult to wash the hydrophobic AST with PBS. In the subsequent experiment, H 2 O 2 When the culture medium is used, the residual AST directly reacts with H 2 O 2 The reaction reduces the amount of H in the system 2 O 2 The concentration of Z / AST and Z / L / C / AST nanospheres significantly reduced the amount of ROS generated in cells compared with the MOD group, decreasing by 29.8% and 70.8%, respectively. Compared with Z / AST nanospheres, Z / L / C / AST nanospheres were more effective in inhibiting the generation of ROS in oxidative stress cells, a result that was consistent with the trend of the cell absorption experiment results.

[0204] The digestion products of free AST had no significant effect on the cellular ROS content (P>0.05). Since the substances produced after simulated gastrointestinal digestion or some active molecules originally present in the digestive fluid can cause toxic effects on small intestinal epithelial cells, the experimental concentration of the simulated digestion products was 15μL / mL. In addition, after simulated gastrointestinal digestion, the low bioavailability (3.9%) of AST resulted in the AST content in this experimental system failing to reach a significant effect concentration. The digestion products of Z / AST and Z / L / C / AST nanomicrospheres significantly reduced the amount of ROS generated in oxidatively damaged cells, and the digestion products of Z / L / C / AST nanomicrospheres had a stronger effect, which was consistent with the results of bioavailability. The above results show that loading AST in Zein or Zein-Lecithin-COS complexes can enhance its inhibitory effect on ROS generation in oxidative stress cells. And the Zein-Lecithin-COS complex loaded with AST has the best effect.

[0205] (9) Effects of nanoparticles on the activity of antioxidant enzymes in Caco-2 cells damaged by oxidation: Effects of free AST, nanoparticles, and their digestion products on the activity of SOD and CAT in Caco-2 cells. Fig.33 Compared with the CON group, the MOD group had significantly lower H 2 O 2 The activities of SOD and CAT in cells treated with free AST were significantly increased (P<0.01). Compared with the MOD group, the activities of SOD and CAT in cells treated with free AST were not significantly increased (P>0.05), which was because the hydrophobicity of AST inhibited the absorption of AST by cells, resulting in the inability of AST to effectively exert antioxidant activity in cells. Compared with the MOD group, both Z / AST and Z / L / C / AST nanomicrospheres significantly increased the activities of SOD and CAT in cells, among which the activity of SOD increased by 30.5% and 73.1%, and the activity of CAT increased by 14.1% and 20.7%. The antioxidant effect of Z / L / C / AST nanomicrospheres was significantly higher than that of Z / AST nanomicrospheres, which was consistent with the results of cell absorption experiments. The digestion products of free AST had no significant effect on the content of cellular ROS (P>0.05). However, the digestion products of Z / AST and Z / L / C / AST nanomicrospheres significantly increased the activities of SOD and CAT in oxidatively damaged cells, and the digestion products of Z / L / C / AST nanomicrospheres had higher antioxidant activity, which was consistent with the results of bioavailability. This suggests that the Zein-Lecithin-COS complex is a suitable delivery system to improve the antioxidant activity of AST.

[0206] (10) Effects of nanoparticles on MDA in Caco-2 cells with oxidative damage: Effects of free AST, nanoparticles and their digestion products on SOD and CAT in Caco-2 cells with oxidative damage. Fig.34 As shown. The MDA level in the MOD group was significantly higher than that in the CON group (P<0.01). Compared with the MOD group, neither free AST nor its digestion products significantly reduced the MDA content in oxidatively damaged cells (P>0.05). Compared with the MOD group, both Z / AST and Z / L / C / AST nanomicrospheres significantly reduced the MDA content in cells, with the nanomicrospheres reducing by 13.8% and 29.4%. The digestion products of Z / AST and Z / L / C / AST nanomicrospheres also significantly reduced the MDA level in oxidatively damaged cells. And Z / L / C / AST nanomicrospheres and their simulated digestion products showed higher cellular antioxidant levels, which was consistent with the results of cell absorption experiments and bioavailability. This further indicates that the Zein-Lecithin-COS complex is a suitable delivery carrier for improving the antioxidant activity of AST.

[0207] (11) Effects of nanospheres and their simulated digestion products on HepG2 cell viability: Effects of different concentrations of Z / AST and Z / L / C / AST nanosphere delivery systems and their simulated digestion solutions as well as OA on HepG2 cell viability. Fig.35 shown.

[0208] like Fig.35 As shown in A and B, Z / AST and Z / L / C / AST nanosphere delivery systems did not produce significant toxicity to HepG2 cell viability at concentrations of 0-500 μL / mL (cell viability > 90%). Fig.35 Data D and E show that the cytotoxicity of the sample of the nanosphere delivery system increased significantly after simulated gastrointestinal digestion. When the concentration of the digestive fluid reached 50 μL / mL, the cell viability of the simulated digestion products of the Z / AST and Z / L / C / AST nanosphere delivery systems was less than 50%. This result shows that simulated gastrointestinal digestion can induce cytotoxicity. When the concentration of the digestive fluid was 0-25 μL / mL, the cell viability of the two nanosphere simulated digestion products was greater than 75%, so the content of the digestive fluid was selected in the range of 0-25 μL / mL in subsequent experiments. Effect of OA on HepG2 cell viability Fig.35 C. The results showed that when the OA concentration was 0-0.5 mM, the cell viability was not significantly affected (P>0.05) and was greater than 90%. When the OA concentration reached 1 mM, the cell viability changed significantly (cell viability <75%), indicating that high concentrations of oleic acid would have a certain toxic effect on cells. Subsequent experiments used 0.5 mM oleic acid as the upper limit of the induction concentration of the cell high-lipid model.

[0209] (12) Effects of Nanoparticles and Their Simulated Digestion Products on Lipids in a Hyperlipidemic Cell Model

[0210] Effects of nanoparticles and their digestion products on blood lipid levels in hyperlipidemia model cells Fig.36 shown. Fig.36 The data showed that the induced model group (MOD) increased the levels of TG, TC and LDL-C in HpeG2 cells and decreased the content of HDL-C.

[0211] Fig.36 In A, compared with the MOD group, free AST had no significant effect on the level of intracellular TG (P>0.05). Fig.36 Free AST in B, C, and D also had no significant effect on the levels of TC, LDL-C, and HDL-C (P>0.05). This is because the hydrophobicity of AST makes it difficult for most of the AST in the experimental group to enter HepG2 cells and exert its biological activity. Fig.36 A, B, and C show that compared with the MOD group, Z / AST and Z / L / C / AST nanoparticles and their simulated digestion products significantly reduced the levels of TG and TC in the hyperlipidemia cell model, and significantly increased the content of HDL-C. After the cells were treated with Z / AST and Z / L / C / AST nanoparticles, their TG content decreased by 15.1% and 42.5%, TC levels decreased by 13.2% and 47.8%, and HDL-C content increased by 34.9% and 100.0%. Fig.36 In D, only Z / L / C / AST nanoparticles treated high-lipid cells, and their cellular LDL-C levels were significantly lower than those in the MOD group. The other experimental groups showed similar trends to TG but no significant differences (P>0.05). The experimental results of TG, TC, HDL-C and LDL-C showed that Z / AST and Z / L / C / AST nanoparticles increased the lipid-lowering activity of free AST, and the introduction of Lecithin did not cause abnormal lipid accumulation in cells.

[0212] After treatment with the digestion products of Z / AST and Z / L / C / AST nano-microspheres, the production of TG and TC in hyperlipidemia model cells was significantly inhibited, and the production of HDL-C was significantly promoted, but the free AST simulated digestion products had little effect on the blood lipid level in hyperlipidemia model cells. In addition, the LDL-C content in the cells did not decrease significantly, but the inhibitory ability of the Z / L / C / AST nano-microsphere digestion fluid on LDL-C was higher than that of the Z / AST nano-microsphere simulated digestion fluid. And the digestion products of Z / L / C / AST nano-microspheres have higher lipid-lowering activity, which is consistent with the results of bioavailability.

[0213] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.

[0214] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing astaxanthin-loaded nanoparticles, characterized in that: The following steps are involved: S1, dissolving zein in an ethanol solution, then adding lecithin and stirring to obtain a zein-lecithin complex; S2, adding astaxanthin to the zein-phosphatidylcholine complex and stirring, and then using water as an anti-solvent to prepare zein-phosphatidylcholine-astaxanthin nanoparticles by an anti-solvent method; S3, adding zein-phosphatidylcholine-astaxanthin nanoparticles into the chitosan oligosaccharide solution, stirring, and adjusting the pH to 4.0 to obtain nanoparticles loaded with astaxanthin.

2. The preparation method according to claim 1, characterized in that The mass ratio of the zein to the lecithin is 1:

1.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the lecithin to the chitosan oligosaccharide is 2:

1.

4. The preparation method according to claim 1, characterized in that: The step S1 is to dissolve zein in an ethanol solution, magnetically stir at 500 rpm for 1 hour, then add lecithin and stir at 500 rpm for 1 hour to obtain a zein-lecithin complex.

5. The preparation method according to claim 1, characterized in that: The step S2 is to add astaxanthin to the zein-phosphatidylcholine complex and stir for 10 minutes at 500 rpm, then take 20 mL and add it to 60 mL of water to form a dispersion, stir the dispersion at 500 rpm for 15 minutes, remove the remaining ethanol from the dispersion in a rotary evaporator, and finally centrifuge at 730×g for 15 minutes to remove large particles and insoluble astaxanthin, and adjust the pH of the dispersion to 4.0 to obtain zein-phosphatidylcholine-astaxanthin nanoparticles.

6. The preparation method according to claim 1, characterized in that: In step S3, the stirring is performed at 500 rpm for 5 min.

7. The preparation method according to claim 1, characterized in that: In the step S3, the final concentration of the chitosan oligosaccharide solution is 5 mg / mL.

8. The astaxanthin-loaded nanoparticles prepared by the preparation method according to any one of claims 1 to 7.

9. The astaxanthin-loaded nanoparticles according to claim 8, characterized in that: The nano-microspheres loaded with astaxanthin are of a core-shell structure, with a particle size of 141.0 nm, a PDI of 0.133, and a Zeta potential of 23.7 mV; and the embedding rate of astaxanthin in the nano-microspheres loaded with astaxanthin is greater than 99.0%.

10. Use of the astaxanthin-loaded nanoparticles according to claim 8 or 9 in delivering astaxanthin.

Citation Information

Cited By

  • A multi-level astaxanthin complex, its preparation method and application

    CN120305235B